THE INFLUENCE OF ACCOUNTABILITY AND TRANSPARENCY ON BUDGET MANAGEMENT: STUDY AT PUBLIC HEALTH CENTER BANDAR LAMPUNG - Siti Khoirina; Rosilawati (Peradaban Journal of Economic and Business, 2022)
This research was conducted to determine and prove the effect of Accountability and Transparency as independent variables to Budget Management as the dependent variable.The population in this research is the entire Public Health Center Budget Manager in Sukabumi District, Bandar Lampung, with a total of 48 employees. This research uses  saturated sampling. Based on the results of this study it is known that Accountability and Transparency has a significant effect on Budget Management simultaneously at Puskesmas in Sukabumi District, Bandar Lampung.